1999
DOI: 10.3109/01480549908993174
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and Humoral Immunity Assessment of Octamethylcyclotetrasiloxane (D4) Following a 28-day whole body Vapor Inhalation Exposure in Fischer 344 Rats

Abstract: Octamethylcyclotetrasiloxane, D4, is a low viscosity, silicone fluid consisting of four dimethyl-siloxy units ((CH3)2SiO)4 in a cyclic structure. It is primarily used as a building block in the industrial synthesis of long chain silicone polymers. The combination of D4 with decamethylcyclopentasiloxane (D5) is commonly referred to as cyclomethicone which has a wide range of applications as a formulation aid in personal care products. To extend the existing database regarding the biological activities of D4, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…In a variety of in vivo and in vitro immunotoxicological studies, D4 was not found to significantly affect systemic immune responses. D4 was not immunotoxic in an inhalation and oral gavage study with F344 rats; however, thymus weight decreased in relation to D4 dosing (Klykken et al, 1999;Naim et al, 1995a;Nicholson et al, 1996b). D4 mixed with bovine serum albumin in an intramuscular study with dark Agouti rats (Nicholson et al, 1996a) and subcutaneous study with A/J mice resulted in a moderate humoral adjuvant effect with intense inflammation evident at the site of injection (DCC, 2001b;Naim et al, 1995b).…”
Section: Othermentioning
confidence: 99%
“…In a variety of in vivo and in vitro immunotoxicological studies, D4 was not found to significantly affect systemic immune responses. D4 was not immunotoxic in an inhalation and oral gavage study with F344 rats; however, thymus weight decreased in relation to D4 dosing (Klykken et al, 1999;Naim et al, 1995a;Nicholson et al, 1996b). D4 mixed with bovine serum albumin in an intramuscular study with dark Agouti rats (Nicholson et al, 1996a) and subcutaneous study with A/J mice resulted in a moderate humoral adjuvant effect with intense inflammation evident at the site of injection (DCC, 2001b;Naim et al, 1995b).…”
Section: Othermentioning
confidence: 99%
“…According to Klykken et al, 18 the second largest use of cyclotetrasiloxane is in personal care products, such as, antiperspirants, deodorants, skin creams, and shampoos. In these applications, it is commonly blended with cyclopentasiloxane and is referred to as cyclomethicone.…”
Section: Chemistrymentioning
confidence: 99%
“…D 4 is also used as a building block in the industrial synthesis of long chain silicone polymers. 18…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations